Aktivitas Biji Klabet (Trigonella foenum-graecum L.) terhadap Pertumbuhan dan Apoptosis Sel Kanker Payudara MCF-7 - KURNIA AGUSTINI; FRANS SUYATNA; NURJATI CHAIRANI SIREGAR; WAHONO SUMARYONO (JURNAL ILMU KEFARMASIAN INDONESIA, 2013)
Fenugreek seed (Trigonella foenum-graecum L.) is one of Indonesian medicinal plant with many known activities such as antidiabetic, antihypercholesterolemia, phytoestrogen and anticancer. Fenugreek seed contains steroidal sapogenines (i.e. diosgenin, yamogenin, gitogenin, tigogenin and trigoneoside), alkaloid trigonellin and flavonoid (i.e vitexin, orientin). This experiment was carried out to investigate the cytotoxic activity and its potency to induce apoptotic on breast cancer cell line, MCF-7. Cytotoxic activity was carried out by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium) method. Fenugreek seed was prepared by extraction (methanolic and ethanolic extract) and fractionation using solvents with different polarity (hexane, ethylacetic, buthanolic and water fractions). The potency of apoptotic induction assay was carried out using flowcytometric method staining with propidium iodide (20μg/mL) on 100 ppm sample. Apoptotic potency was evaluated based on % population of cells in subG0/G1 phase. Results showed that ethylacetic fraction has the lowest IC50 (41.81 ppm) and significantly (p<0.05) increase % population of cells in subG0/G1 phase (20.87%) on 100 ppm concentration. It is concluded that fenugreek seed posses cytotoxic activity and potency of apoptotic induction on MCF-7 cells.